Empowering Indonesian Migrant Workers in Hong Kong with Self-Esteem Development: english - Sri Utaminingsih; Saiful Anwar; Shella Rachmawaty (Communautaire: Journal of Community Service, 2024)
This study aims to enhance the self-confidence and psychological well-being of Indonesian migrant workers (TKI) in Hong Kong. The initiative was developed in response to the challenges faced by TKI, including discrimination, social isolation, and cultural adaptation difficulties, which often lead to low self-esteem and stress. Using a participatory qualitative research method, the study collected data through observations, in-depth interviews, and participant feedback during a series of training and counselling sessions focused on stress management, communication skills, and community building. The findings reveal significant improvements in participants' confidence, with notable increases in their ability to communicate effectively, manage stress, and build social support networks. These results underscore the importance of integrating training with social support mechanisms to address the multifaceted challenges faced by migrant workers. The study contributes to the literature on migrant worker empowerment by offering a replicable model for similar interventions in other contexts.